Pengembangan Alternatif Transportasi Berbasis Cable Train Untuk Solusi Sistem Pengangkutan (Studi Kasus Angkutan Penumpang Dan Barang Di Area Gunung Ijen) - ., Jamaludin; Fadilah, Lina Nur (Indonesian Railway Journal, 2017)
This scientific focus on development system of cable train  building  in  Ijen   Mountain  area, Banyuwangi Regency, East Java that is functioned as supporter of goods  and  passanger?s  transport that is expected become the solution  for  problem  solving  of goods  transport  like  the  sulphur  that has been left behind, can attract the interest  of tourist from inside and outside of country,  increase the  region  income  and  increase  economic  quality  of  people  around  Ijen  Mountain.  This  scientific is appliying for comparation research of  methodology.  The  result  of  this scientific suggesst that cable train can be build immediately in Ijen Mountain, government pay more attention of transport system in Ijen Mountain that has been left behind  and  consider  to   build  cable  train  in  Ijen mountain.